Instruments of Devotion The Practices and Objects of Religious Piety from the Late Middle Ages to the 20th Century. - Laugerud, Henning; Skinnebach, Laura Katrine (Santa Barbara : Aarhus University Press, 2007)
Belief and religion are returning as focal concerns in modern philosophical debate. Interestingly, this 'religious turn' is most clearly seen in so-called post-modern or post-structuralist thinking. Today we are witnessing the dissolution of philosophical theories such as positivist scientism and Marxism, which thought they had definitively liquidated religion. After modernity, there are no more strong philosophical reasons either to be an atheist refusing religion or to be a theist refuting science. The above, or similar, attitudes form a common point of departure for all the contributors to.
IntroductionTheories of vision; Sight as Knowledge; Images and Visions; Modes of vision and the familiarity of Images; 'the solace of his image':; Introduction; Images as presence: the Veronica-legend as an introductory case; Real presence: Eucharistic vision; Physical presence: close encounters with the Holy; In the presence of the divine: relations between man and the Holy in late medieval donator images; Concluding remarks: representations versus experiences of presence; Bibliography; Notes on contributors
Description based upon print version of record.
Keywords: Devotional objects -- Catholic Church; Worship -- History; Spiritual life -- Christianity -- History of doctrines -- Middle Ages, 600-1500.; RELIGION / Christian Life / General; Electronic books